Analisis Semiotika Riffaterre dalam Puisi "Hiya Fil Masāi Waḥīdatin” Karya Mahmoud Darwish - Raden Muhammad Ardiansyah Kurniawan; Ridwan Ritonga; Aminuddin Hrp, Arpin; Kastrawi, Puji; Manan Nasution, Abdul; Ismail (Kajian Linguistik dan Sastra, 2024)
This study aims to uncover the deepest meaning of language signs in Mahmoud Darwish's Hiya Fil Masāi Waḥīdatin poetry using Micheal Riffaterre's semiotic theory. This research uses a descriptive method with qualitative analysis. The source of this research data is the poerty Hiya Fil Masāi Waḥīdatin which consists of 34 lines. In interpreting signs in poetry, Riffaterre offers two concepts of reading. The first stage is through heuristic reading, then hermeneutic reading, followed by models, variants, matrices, as well as hypograms. The results of this study were found in heuristic readings of the meanings that are still ambiguous and heterogeneous. On the other hand, in hermeneutic reading, the model that is in the form of "sadness" is found in stanzas 1 and 2. These two stanzas represent the entire content of the poem, for the whole stanza reflects a man's sorrow for him (his country). Then the model was developed into variants namely sympathy and struggle. The matrix in this poem describes "the meaning of a homeland". The hypogram of Hiya Fil Masāi Waḥīdatin poetry is backed by two poetries, namely Yaumiyātu Jurḥ Filasṭīnī and Al-Waṭan ‘an Syain which have the meaning of suffering from alienation and longing so that a sense of struggle arises.